2023
DOI: 10.1021/acs.jafc.3c00912
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin Maintains Barrier Integrity by Reducing the Expression of ABCG2 in Colonic Epithelial Cells

Abstract: Crohn’s disease (CD) is a relapsing and chronic inflammatory bowel disease. Recent advances have highlighted that dysfunction of the barrier function formed by a polarized monolayer of columnar epithelial cells plays a crucial role in the pathophysiology of CD. At present, we reported that diosmetin increased cell viability by reducing the levels of TNFα and IL-6 in lipopolysaccharide (LPS)-treated colonic epithelial Caco-2 cells. Meanwhile, diosmetin conferred a direct effect on maintaining barrier integrity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The initial pathological change that strengthens injury and inflammation is thought to be functional loss of epithelial cell barrier integrity, which results in the migration of luminal antigens into the submucosa, exposing lamina propria immune cells to these antigens and eliciting an inflammatory response in the intestine [ 72 ]. One of A. muciniphila 's key mechanisms is based on its regulation of the host intestinal barrier via promotion of TJ protein expression (ZO-1 and Claudin-1 mRNA) [ 73 ], thereby inhibiting the entry of intestinal bacteria-borne endotoxin into the blood and relieving chronic inflammation in vivo [ 71 ]. Several studies have found that A. muciniphila could improve intestinal barrier integrity [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial pathological change that strengthens injury and inflammation is thought to be functional loss of epithelial cell barrier integrity, which results in the migration of luminal antigens into the submucosa, exposing lamina propria immune cells to these antigens and eliciting an inflammatory response in the intestine [ 72 ]. One of A. muciniphila 's key mechanisms is based on its regulation of the host intestinal barrier via promotion of TJ protein expression (ZO-1 and Claudin-1 mRNA) [ 73 ], thereby inhibiting the entry of intestinal bacteria-borne endotoxin into the blood and relieving chronic inflammation in vivo [ 71 ]. Several studies have found that A. muciniphila could improve intestinal barrier integrity [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that elucidating the mechanisms underlying barrier dysfunction and permeability defects has great potential in the treatment of CD [108]. Liu et al discovered that in LPS-treated colorectal adenocarcinoma (Caco-2) cells and TNBS-induced CD model mice, Dios treatment was effective in decreasing epithelial permeability and improving the expression of proteins related to barrier integrity (such as ZO-1, occludin, and claudin-1) [53]. This indicated that Dios has great potential in the treatment of CD.…”
Section: Intestinementioning
confidence: 99%